CURRENT PROBLEMS OF VULVAR CANCER. (World Bulletin of Public Health, 2025)
Vulvar cancer represents a rare but serious malignancy within the spectrum of gynecological cancers. Despite progress in diagnosis and treatment, late detection, limited awareness, and psychosocial implications continue to hinder outcomes. This article explores the epidemiology, risk factors, diagnostic difficulties, therapeutic challenges, and emerging strategies in vulvar cancer management, highlighting current problems and possible solutions for improving patient care and survival.
Keywords: Vulvar cancer; gynecologic oncology; human papillomavirus